RESIN KEY HANGER MAKING TRAINING IN EFFORTS TO IMPROVE ECONOMIC INDEPENDENCE FOR TARUNA CORAL, SUKAKARYA VILLAGE, MEGAMENDUNG SUB-DISTRICT, BOGOR DISTRICT - Amalina Shomami; Mochammad Sholeh (Politeknik Negeri Media Kreatif, 2019)
Community service activities for the 2019 D IV Manufacturing Study Program are motivated by the cultural conditions of the community that have not prioritized education as a means of supporting economic independence and the community's need for technical training following village potential. The current condition, most of the residents of Sukakarya village are casual workers and ojeg workers, even though these jobs cannot provide economic independence, and their income is still minimal. The priority of this training is to increase insight into the importance of education and skills of young people in making critical chains with resin media. This training method is discussion and practice. Meetings were held in an effort to open up insights that education is essential. After that, the process of learning the way of making key hanging made from the resin was carried out, which was guided by the lecturers and students. This training facility includes rooms, module equipment, tools, and critical materials, trainers consisting of lecturers and students, transportation, and consumption. The purpose of this community service, in general, is the socialization of the importance of education so that it is expected to be able to change the perspective of the community. Besides, it also increases simple technical skills, namely the manufacture of resin key hanging.